Effect of motility on the transport of bacteria populations through a porous medium - Creppy, Adama (2019)
The role of activity on the hydrodynamic dispersion of bacteria in a model porous medium is studied by tracking thousands of bacteria in a microfluidic chip containing randomly placed pillars. We first evaluate the spreading dynamics of two populations of motile and nonmotile bacteria injected at different flow rates. In both cases, we observe that the mean and the variance of the distances covered by the bacteria vary linearly with time and flow velocity, a result qualitatively consistent with the standard geometric dispersion picture. However, quantitatively, the motile bacteria display a systematic retardation effect when compared to the nonmotile ones. Furthermore, the shape of the traveled distance distribution in the flow direction differs significantly for both the motile and the nonmotile strains, hence probing a markedly different exploration process. For the nonmotile bacteria, the distribution is Gaussian, whereas for the motile ones, the distribution displays a positive skewness and spreads exponentially downstream akin to a Γ distribution. The detailed microscopic study of the trajectories reveals two salient effects characterizing the exploration process of motile bacteria: (1) the emergence of an "active" retention effect due to an extended exploration of the pore surfaces and (2) an enhanced spreading at the forefront due to the transport of bacteria along "fast tracks" where they acquire a velocity larger than the local flow velocity. We finally discuss the practical applications of these effects on the large-scale macroscopic transfer and contamination processes caused by microbes in natural environments.